Circadian Variation in the Onset of Placental Abruption - Masanao Ohhashi; Seishi Furukawa; Hiroshi Sameshima (Journal of Pregnancy)
Objective. To determine circadian variation in the onset of placental abruption. Methods. A retrospective study involving 115 placental abruptions, divided into four subgroups based on initial symptoms comprising abdominal pain, vaginal bleeding, both abdominal pain and bleeding, or other symptoms. The time of the initial symptom was considered the disease onset. We analyzed the frequency of disease onset and adverse perinatal outcome including perinatal death relative to the daily four 6-hour intervals. Results. Abdominal pain displayed significant circadian variation regarding the period of onset with higher levels from 0:00 AM to 6:00 AM (65%) compared with 0:00 PM to 6:00 PM (24%, p<0.01). Vaginal bleeding did not display significant circadian variation (p=0.45). Adverse perinatal outcome showed significant circadian variation with a higher occurrence of perinatal death from 0:00 AM to 6:00 AM (35%) compared with 0:00 PM to 6:00 PM (0%, p<0.01). After adjustment using variables of abdominal pain and time period, both variables significantly affected perinatal death (odds ratio: 13.0 and 2.2, resp.). The risk of adverse perinatal outcome increased significantly when abdominal pain occurred, except for the period 0:00 PM to 6:00 PM (OR, 9.5). Conclusion. Placental abruption beginning with abdominal pain has circadian variation.